Application by the Supreme Court of the Republic of Article 199 of the Penal Code on the Violation of Minors - Ríos de Romaña, Orlando de los (1974)
This article analyzes the Peruvian Supreme Court decisions related to article 199 of the Penal Code and related provisions on the crime of alleged rape of minors. In this context, the author discusses the interpretation of the law, the protected legal right, the active and passive subject of the crime, culpability, consummation, attempt, the circumstances that aggravate the repression, the criminal action and the penalty. He also highlights the controversy over whether a minor can be considered the active subject of his own rape, which generates different interpretations and positions in the opinion and resolutions of the Supreme Court. Additionally, the author addresses the confusion regarding the application of Article 200 of the Penal Code in cases of acts analogous to sexual acts, previously addressing the discussion on the protected legal right, which may be sexual freedom, the psychophysiological integrity of the minor, modesty or sexual safety. The article also discusses the different aspects related to criminal action in crimes against sexual honor, the minimum age for marriage and the penalty in specific cases, as well as the importance of considering psychiatric treatment for the perpetrators of the crime. Finally, a case is presented in which a prison sentence is imposed on two defendants for a crime related to a minor, discussing the responsibility of the defendant in crimes against sexual honor and the obligation to provide the offended party, even in cases of attempt, concluding that the law does not make distinctions and that the Supreme Court has acted in accordance with the law in its resolutions.